The Influence of Teacher’s Role on Students’ Motivation to Learn Fiqh at Nurul Iman Islamic Boarding School: A Quantitative Study - Dadi Sutrisna; aniyatussaidah aniyatussaidah; Sadarela; Retno Ayu Atikah Dewi; Suprihatin; Mulyadi (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2025)
Qur’anic education In the context of globalization and the demand for competitive human resources, education serves as a fundamental tool for fostering intellectual and moral development. Islamic education, particularly the teaching of Fiqh, plays a crucial role in shaping students' religious commitment and daily worship practices. This study aims to examine the influence of the teacher's role on students’ motivation to learn Fiqh at Nurul Iman Islamic Boarding School. Grounded in the framework of Self-Determination Theory, the research explores how elements such as teacher encouragement, classroom engagement, and personal connection contribute to students’ intrinsic motivation. This research employs a quantitative, correlational method using an ex-post facto design. A sample of 30 students from five dormitories at Nurul Iman Islamic Boarding School was selected. Data were collected through questionnaires and analysed using simple linear regression. The results reveal a statistically significant influence of the teacher’s role on students’ learning motivation, with an R value of 0.686 and R² of 0.470, indicating that 47% of the variance in student motivation is explained by the teacher's role. These findings affirm that the teacher is not merely a transmitter of knowledge, but a critical agent in fostering a motivational learning environment. Effective Fiqh teachers act as mentors and motivators, using praise, rewards, emotional support, and active guidance to cultivate religious awareness and student engagement. The study underscores the necessity of empowering teachers with strategies that fulfil students’ psychological needs for autonomy, competence, and relatedness, thus enhancing their motivation to engage in religious learning meaningfully.